Temporal and spatial variation in the quality of surface water in the subwatershed of the Virilla river (Costa Rica) between 2006 and 2010 - Herrera, Jorge (2013)
In this work, we considered data of 25 water quality variables collected between January 2006 to December 2010 at 64 monitoring sites along the Virilla River Subbasin in Costa Rica. Factor analysis identified two potential pollution sources that explained 80.9% of the total variance in LP, two potential pollution sources that explained 77.1% of the total variance in MP, and two potential pollution sources that explained 67.8% of the total variance in HP. Most water quality variables were influenced primarily by pollution due to industrial wastewater, agricultural activities and urban runoff.